2021
DOI: 10.1177/21925682211018467
|View full text |Cite
|
Sign up to set email alerts
|

Longer Screws Can Reduce the Stress on the Upper Instrumented Vertebra With Long Spinal Fusion Surgery: A Finite Element Analysis Study

Abstract: Study Design: A finite element analysis study. Objective: Of proximal junctional failure, upper instrumented vertebra (UIV) fracture can causes severe spinal cord injury. Previously, we reported that higher occupancy rate of pedicle screw (ORPS) at UIV prevented UIV fracture in adult spinal deformity surgery; we had not yet tested this finding using a biomechanical study. The purpose of present study was to measure the differences in loads on the UIV according to the length of PS and ORPS. Methods: We designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Therefore, the abnormal spinal loading caused by ASD and the individual variation of degeneration were not considered. This methodology was consistent with the previous FE studies focusing on the performance of different instrumentations and instrumentation-related problems in ASD ( Buell et al, 2019 ; He et al, 2021 ; Oe et al, 2021 ; Leszczynski et al, 2022 ; Son et al, 2022 ). Further studies should construct and use ASD patient-specific FE models to elucidate the clinical significance of the various instrumentations.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the abnormal spinal loading caused by ASD and the individual variation of degeneration were not considered. This methodology was consistent with the previous FE studies focusing on the performance of different instrumentations and instrumentation-related problems in ASD ( Buell et al, 2019 ; He et al, 2021 ; Oe et al, 2021 ; Leszczynski et al, 2022 ; Son et al, 2022 ). Further studies should construct and use ASD patient-specific FE models to elucidate the clinical significance of the various instrumentations.…”
Section: Discussionsupporting
confidence: 90%
“…However, aiming for ORPS > 80% and avoiding bicortical screw placement can be challenging. Oe et al 12 reported that a 5 mm change in screw length can change ORPS by more than 10%. Therefore, the use of an intraoperative navigation system may be useful to achieve optimal ORPS.…”
Section: Discussionmentioning
confidence: 99%
“…Strengthening bone density is considered an important measure,8,9 but some reports indicate that bone density and PJF are not related 5,10,11. Recently, Oe et al 12 named the ratio of pedicle screw (PS) length to the anterior-posterior diameter of the vertebral body at the UIV as the occupancy rate of a pedicle screw (ORPS) and, using finite element analysis, reported that the stress on the UIV decreased the most when the ORPS was 81.8% or more. However, if the screw is too long, it can penetrate the anterior wall of the UIV.…”
mentioning
confidence: 99%
“…Matsukawa et al suggest that longer screws increase the degree of bone contact, and the use of deeper screw insertion and larger diameter screws is justified for better stability ( 26 ). Oe et al pointed out that to some extent, the longer the pedicle screw, the greater the biomechanical stability, and the stability decreases after a certain length ( 27 ). However, it has been suggested that intermediate short-pedicle screw fixation can provide a similar level of stability to intermediate long-pedicle screw fixation, with no significant difference in the stress associated with bending, extension, and left–right axial rotation ( 28 ).…”
Section: Discussionmentioning
confidence: 99%